Extraction of Bioactive Component from Herbal Anoectochilus formosanus Hayata by Microwave, Ultrasound and Lactic Fermentation - Le Thi Kim Ngan; Nguyen Thi Ly; Nguyen Thi Tham; Dang Thi Kim Thuy; Do Dang Giap; Lieu My Dong (Turkish Journal of Agriculture: Food Science and Technology)
Anoectochilus formosanus Hayata was demonstrated to have a benefit healthy due to containing active pharmaceutical ingredients. However, A. formosanus is usually processed to produce tea bags which would destroy the bioactive compounds because of the processing procedure. The aim of this study was to evaluate the influence of extracted methods including microwave-assisted extraction (MAE), ultrasound-assisted extraction (UAE), and fermentation by Lactobacillus acidophilus ATCC-4356 to extract the active pharmaceutical ingredients from A. formosanus. The extracted liquid was analyzed total phenolics, total polysaccharide, and antioxidant activity. The results showed that three methods have a positive effect on the extraction of bioactive compounds of A. formosanus in which the fermentation showed the best result. The total phenolic content, total polysaccharide content and antioxidant capacity that extracted by the fermentation method were 11.762 mg GAE/g; 48.914 mg GE/g, and 1.582 mgVit C/g compare to MAE and UAE which were 7.818 mg and 8.128 GAE/g samples; 41.22 and 37.91mg GE/g samples; 1.032 and 1.163 mgVit C/g respectively. The A. formosanus fermentation method by L. acidophilus promotes bioactive compounds of high biological value. This study would suggest a novel use of lactic fermenting A. formosanus in the production of functional foods.